2011
DOI: 10.1016/j.hrthm.2011.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Increased left ventricular mass and decreased left ventricular systolic function have independent pathways to ventricular arrhythmogenesis in coronary artery disease

Abstract: Background Following myocardial infarction, individual patients can have wide variations in extent of LV systolic dysfunction and increased LV mass. Both affect risk of sudden cardiac death but only LV ejection fraction is used for risk prediction. Objective We evaluated the independent as well as additive contributions of increased LV mass and decreased LV ejection fraction to sudden cardiac death in the general population. Methods In the ongoing Oregon Sudden Unexpected Death Study, we studied consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 30 publications
1
52
0
2
Order By: Relevance
“…47,48 Both LVH and cardiac fibrosis have been implicated in increasing the risk for sustained ventricular arrhythmias and the predisposition to SCD. [49][50][51][52][53] Kidney disease is also associated with vascular disease including calcification and stiffening of the blood vessels. [54][55][56][57] Declines in eGFR and endothelial dysfunction are inter-related processes that diminish vascular elasticity and subsequently increase ischemic events.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…47,48 Both LVH and cardiac fibrosis have been implicated in increasing the risk for sustained ventricular arrhythmias and the predisposition to SCD. [49][50][51][52][53] Kidney disease is also associated with vascular disease including calcification and stiffening of the blood vessels. [54][55][56][57] Declines in eGFR and endothelial dysfunction are inter-related processes that diminish vascular elasticity and subsequently increase ischemic events.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…In addition to providing a test of the usefulness of the K-P model for field intensities close to the range of those attained during defibrillation, this study also addresses a point of potential clinical importance, as cardiomyocyte hypertrophy is commonly associated with conditions that increases the probability of cardiac fibrillation and sudden death occurrence (e.g., Bender et al, 2012;Brouwer et al, 2011;Reinier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al12 found that the odds of duty‐related SCD in firefighters aged ≤45 years increased nearly 5‐fold in the presence of cardiomegaly. In population‐based studies, LVH has been shown to be a strong independent predictor of cardiovascular mortality, including SCD,14, 15 and the risk of SCD increased with increasing LV mass 14. In addition, LVH is associated with an increased risk of ventricular arrhythmias in the absence of CHD, with a graded and continuous relationship between LV mass or wall thickness and occurrence and complexity of ventricular arrhythmia 29.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of LVH and cardiomegaly have not received nearly as much attention as CHD in contributing to sudden cardiac events. LVH has been shown to be a strong independent predictor of SCD in the general population,14, 15 but its prognostic power within the general fire service has not been documented. A recent case–control study determined that cardiomegaly (defined as heart weight >450 g), which was found in 61% of SCD cases, was associated with a 5‐fold increased risk of SCD among young (aged ≤45 years) firefighters 12.…”
Section: Introductionmentioning
confidence: 99%